Phase-lag effects in skin tissue during transient heating - Kumar, Rajneesh; Vashishth, Anil K.; Ghangas, Suniti (Zielona Góra: Uniwersytet Zielonogórski)
A three-phase-lag (TPL) model is proposed to describe heat transfer in a finite domain skin tissue with temperature dependent metabolic heat generation. The Laplace transform method is applied to solve the problem. Three special types of heat flux are applied to the boundary of skin tissue for thermal therapeutic applications. The depth of tissue is influenced by the different oscillation heat flux. The comparison between the TPL and dual-phase-lag (DPL) models is analyzed and the effects of phase lag parameters and material constant on the tissue temperature distribution are presented graphically.
Keywords: bioheat transfer; skin tissue; three-phase-lag; Laplace transform; transient heating